Application of the Dijkstra and Floyd – Warshall Algorithms in Determining the Shortest Route to Tourist Attractions in Toba - Mega Agustina Samosir; Mulyono (Formosa Journal of Science and Technology, 2023)
The Toba Regency Government focuses on developing the tourism sector, because the natural resources in Toba Regency have great potential. The purpose of this research is to determine the shortest route to an effective tourist spot and the time it takes to cover that distance. The method used to determine the shortest route is the Dijkstra and Floyd - Warshall Algorithms. Dijkstra's algorithm aims to choose the best solution from each set of solutions, while the Floyd-Warshall algorithm compares all possible paths on the graph for each vertex. Based on the research results, the shortest route for 24 tourist attractions in Toba produces the same route using both algorithms and a weighted graph is obtained.